Sudden Death Syndrome and Soybean Planting Date - Eric Adee; C. R. Little; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2016)
The effect of soybean planting date on the severity of sudden death syndrome (SDS) and yield were evaluated in two studies at the Kansas River Valley Experiment Field in 2015. One study was established to promote SDS and the other to minimize SDS. In both studies the severity of SDS was greatest with the earlier planting dates, except for the more tolerant variety. The yield was greatest with the earlier planting date, except for the most susceptible variety. The severity of SDS was not as great as had been observed in previous years.
Keywords: sudden death syndrome; soybean; planting date